2017
DOI: 10.3892/mmr.2017.7291
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 is expressed and functional in late endothelial progenitor cells

Abstract: It has been previously demonstrated that lipopolysaccharides (LPS) inhibit the viability, migration, adhesion and in vitro angiogenesis of late endothelial progenitor cells (EPCs). However, the mechanisms underlying this LPS‑induced impairment of late EPC functional activity are unknown. The aim of the present study was to investigate whether Toll‑like receptor 4 (TLR4) is expressed and functional on late EPCs, using late EPCs of 3‑5 passages. Cells were deprived of serum for 24 h prior to experiments and incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In this study, LPS (20 μg/ml) significantly reduced the proliferation, migration, and tube formation of EPCs. This is consistent with Yu et al research, which found that LPS (10 μg/ml) impaired the viability, migration, adhesion abilities, and tube formation of late EPCs ( Yu et al, 2017 ). Compared with the control group, the proliferation and adhesion activities of bone marrow-derived EPCs were impaired in LPS (100 ng/ml) induced group in dose and time dependence ( Li et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, LPS (20 μg/ml) significantly reduced the proliferation, migration, and tube formation of EPCs. This is consistent with Yu et al research, which found that LPS (10 μg/ml) impaired the viability, migration, adhesion abilities, and tube formation of late EPCs ( Yu et al, 2017 ). Compared with the control group, the proliferation and adhesion activities of bone marrow-derived EPCs were impaired in LPS (100 ng/ml) induced group in dose and time dependence ( Li et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the concomitant deregulation of Notch-1 pathways, previously observed in BAV cases 15 , might also justify the reduced numbers of circulating T and B subsets and EPC 14,15 . These two pathways are, indeed, known to play a crucial role in physiological haematopoiesis 29,30 , the physiological release and functionality of progenitors, such as EPC 8,30,31 , as well as in embryological organogenesis and valvulogenesis 1,16,23,30,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that when a relatively high dose of LPS (10 μg/ml) can induce the oxidative stress and impair the survival and proangiogenic abilities of human EPC (Wang et al., 2019; Yu et al., 2017), the relatively low concentration (1–2 μg/ml) of LPS may provide some protective preconditioning effects (Heidarzadeh et al., 2021; Wang et al., 2019). In the present study, we firstly tested the relationship between the LPS concentration and the exosome release which measured by the AChE activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that TLR4 signaling involved in varieties of inflammatory and hypoxic conditions, including atherosclerosis, reperfusion injury, cardiac hypertrophy, pulmonary hypertension, and sepsis (Bauer et al., 2014; Bowman et al., 2017; Cao et al., 2018; Ehrentraut et al., 2011; Ha et al., 2011,). Recently, functional TLR4 was also found expressed on human EPC (He et al., 2010; Heidarzadeh et al., 2021; Yu et al., 2017,), which can induce the downstream signals transduction and modulate the EPC functional performance, including survival and angiogenesis (Heidarzadeh et al., 2021; Wang et al., 2019; Yu et al., 2017). However, the influence of TLR4 on EPC‐derived exosomes (Exo) has never been reported before.…”
Section: Introductionmentioning
confidence: 99%